A flue gas filter material for coal-fired power plants and a preparation method thereof
By using a double MOFs composite adsorbent with amino copper MOF and amino ZIF-8 shell structure in flue gas filtering materials, combining mesoporous γ-alumina and citric acid, the pollution of traditional materials at high temperatures and moisture, SO2, etc. is solved. The problem of reducing denitrification efficiency under the action of substances has achieved efficient and water-stable flue gas filtration effect.
Patent Information
- Application Number
- CN202411198653.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-29
AI Technical Summary
Under the action of high temperature and pollutants such as moisture and SO2, traditional flue gas filter materials have reduced denitrification efficiency and insufficient high temperature resistance.
Using amino copper MOF as the core, the amino ZIF-8 shell structure was grown under the modification of polyvinylpyrrolidone by epitaxial growth method, combining mesoporous γ-alumina and citric acid to form a double MOFs composite adsorbent with a core-shell structure. , and improve the bonding performance through hot pressing composite technology.
It realizes excellent water stability and efficient desulfurization and denitrification properties of flue gas filter materials, and can maintain good filtration performance under high temperature conditions.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flue gas filter materials, in particular to a flue gas filter material for a coal-fired power plant and a preparation method thereof. Background Art
[0002] Bag filter technology is widely used in industry as an effective technology for purifying dusty flue gas due to its excellent separation efficiency and good fine particle collection efficiency level. The quality of bag filter material will directly affect the dust removal effect. On the one hand, various traditional materials are used in bag filters, including glass, ceramics, polytetrafluoroethylene, polyphenylene sulfide, polyethylene, polypropylene and polyamide. It should be pointed out that polyphenylene sulfide is widely used in the market due to its high temperature resistance, resistance to multiple chemical corrosion and relatively economical price. On the other hand, many new electrospun nanofibers, such as polyurethane, polyacrylonitrile, polymethyl methacrylate, polyimide, polytetrafluoroethylene, polyvinyl chloride / polyurethane and polyvinyl alcohol, have been successfully prepared and show effectively enhanced filtration performance. In addition, low resistance and high filtration performance of nanofiber membranes formed by special structures have also been reported.
[0003] However, under actual working conditions, filter bags are subjected to very harsh filtering conditions. First, the temperature of flue gas is very high, but most traditional fibers are not heat-resistant. Therefore, it is of great significance to invent a flue gas filter material with high temperature resistance for coal-fired power plants. Summary of the invention
[0004] The purpose of the present invention is to provide a flue gas filter material for coal-fired power plants and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a flue gas filter material for a coal-fired power plant comprises the following steps:
[0007] S1: add copper sulfate trihydrate, 5-aminoisophthalic acid and tris-benzoic acid into a mixed solvent, disperse by ultrasonication, heat to 85-90°C for reaction for 20-22h, filter, wash alternately with N,N-dimethylformamide and ethanol, and dry under vacuum at 80°C to obtain amino copper-based MOF;
[0008] Furthermore, the mixed solvent is composed of N,N-dimethylformamide, ethanol, and deionized water in a volume ratio of 1:1:1;
[0009] Furthermore, in the amino copper-based MOF, the mass ratio of copper sulfate trihydrate: 5-aminoisophthalic acid: tris-benzoic acid is 1: (0.25-0.5): (0.75-1);
[0010] S2: Add polyvinyl pyrrolidone to methanol and stir evenly, add amino copper-based MOF and zinc nitrate hexahydrate and stir evenly to obtain solution A; add 2-methylimidazole and 2-aminobenzimidazole to methanol and stir evenly to obtain solution B; add solution B to solution A, stir and react for 1.5-2h, filter, wash with methanol, and vacuum dry at 80°C to obtain a composite MOF;
[0011] Furthermore, in the solution A, the mass ratio of amino copper-based MOF: polyvinyl pyrrolidone: zinc nitrate hexahydrate is 1: (0.2-0.4): (0.31-1.24); in the solution B, the mass ratio of 2-methylimidazole: 2-aminobenzimidazole is (0.546-2.18): (0.225-0.902);
[0012] S3: Add the triblock copolymer to anhydrous ethanol, stir for 6-8h, add 65-68wt% nitric acid and aluminum isopropoxide, completely cover the reaction container with a polyvinyl alcohol film, stir at room temperature for 24h, remove the film and place at 60°C to evaporate the solvent, age for 3d, heat the aged product to 700-705°C and calcine for 4-4.5h, crush and sieve to obtain mesoporous γ-alumina;
[0013] Furthermore, in the mesoporous γ-alumina, the mass ratio of triblock copolymer to aluminum isopropoxide is (1-2):(2-4);
[0014] Furthermore, the three front-end copolymers are polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymers;
[0015] Further, the mesoporous γ-alumina particle size is 40-60 mesh;
[0016] Further, the heating rate is 1°C / min;
[0017] S4: adding composite MOF, mesoporous γ-alumina, mesoporous ρ-alumina, citric acid and deionized water into a container and mixing them evenly, adding the mixed slurry into a mold, and vacuum drying at 110° C. for 12 h to obtain a filter layer A;
[0018] Furthermore, the proportions of the components in the filter layer A include, by mass, 100-120 parts of composite MOF, 20-50 parts of mesoporous γ-alumina, 5-24 parts of mesoporous ρ-alumina, 0.012-0.06 parts of citric acid, and 5-20 parts of deionized water;
[0019] S5: immerse the polytetrafluoroethylene filter material in a sodium alginate solution, vacuum filter, take it out, squeeze the filter material with a metal roller to remove excess sodium alginate solution, and vacuum dry it at 60°C for 24 hours to obtain a modified polytetrafluoroethylene filter material; immerse the modified polytetrafluoroethylene filter material in a mixed solution of manganese nitrate and cerium nitrate, vacuum filter, remove it, and vacuum dry it at 200°C for 60 minutes to obtain a filter layer B;
[0020] Furthermore, in the modified polytetrafluoroethylene filter material, the concentration of the sodium alginate solution is 0.8-1.0wt%, and the immersion time is 60-65min; in the filter layer B, the concentration of cerium in the mixed solution is 0.07-0.08mol / L, the molar ratio of manganese to cerium is 6:1, and the immersion time is 60-65min;
[0021] S6: Spraying tourmaline particles onto the surface of filter layer B through a venturi tube and compressed air, immersing the sprayed filter layer B into polytetrafluoroethylene emulsion, taking it out, squeezing the filter material with a metal roller to remove excess polytetrafluoroethylene emulsion, and hot-pressing it with filter layer A coated with polyimide emulsion to obtain a flue gas filter material.
[0022] Furthermore, the spraying method includes spraying tourmaline particles on the surface of the filter layer B through a venturi tube and compressed air; the spraying content of the tourmaline particles is 12.5-15g / cm 2 ; The concentration of the polytetrafluoroethylene emulsion is 10-12wt%; the polyethyleneimine coating thickness on the surface of the filter layer A is 8-10μm; the polyimide emulsion composition includes 70-85wt% polyimide and 15-30wt% polytetrafluoroethylene; the hot pressing composite temperature is 200-210℃, the hot pressing pressure is 1.5-1.6MPa, and the hot pressing time is 30-45s;
[0023] Furthermore, the particle size of the tourmaline is 10.9 μm, and the mass percentage of the components includes 35.21% SiO2, 31.89% Al2O3, 24.33% Fe2O3, 7.34% CaO, and 0.37% MnO.
[0024] Furthermore, the thickness of the polytetrafluoroethylene filter material is 0.47-0.5 mm; the fiber diameter is 0.39-0.51 μm; and the permeability is 2.22-2.24 μm. 2 ×10 -12 .
[0025] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0026] The present invention adopts a method of sodium alginate deposition combined with vacuum filtration to load Mn-based and Ce-based catalysts on the surface and inside of polytetrafluoroethylene filter material. The sodium alginate solution can be fully absorbed by the polytetrafluoroethylene filter material through vacuum filtration, so that Mn / Ce oxides can be better dispersed on the fiber surface and inside of the polytetrafluoroethylene filter material, thereby providing more active sites for the consolidation of Mn / Ce-based catalysts, and having good dust removal activity and denitrification effect. In order to solve the problem that the denitrification efficiency of traditional filter materials is rapidly reduced due to the influence of moisture and SO2 in flue gas, the present invention plans to compound filter materials with excellent water stability and desulfurization performance to prepare a flue gas filter material with excellent desulfurization and denitrification performance, and can be applied to the field of flue gas filtration containing a large amount of moisture.
[0027] The present invention uses copper sulfate trihydrate, 5-aminoisophthalic acid and tris-benzoic acid as raw materials to prepare amino copper-based MOF, uses it as the core, and grows amino ZIF-8 shell structure under the modification of polyvinyl pyrrolidone through epitaxial growth method, and uses solvent thermal synthesis technology to construct a dual MOFs composite adsorbent with core-shell structure from the inside out, which has excellent adsorption and desulfurization performance. On the one hand, the open metal sites, functional groups and electrostatic effects of dual MOFs are used to effectively improve the adsorption performance of SO2. On the other hand, the buffer protection of the outer amino ZIF-8 shell crystal particles and the inhibitory effect of the imidazole ligands in the structure on hydrolysis are used to protect the core amino copper-based MOF, providing excellent water stability for the composite MOF. When the amount of adsorbed water reaches 25wt%, the original characteristics of the MOF as a whole can still be maintained, and the adsorption amount is greatly improved compared with the traditional single MOF adsorbent.
[0028] The present invention uses homemade mesoporous ρ-alumina as a binder, and composite MOF, mesoporous γ-alumina, citric acid, and deionized water as raw materials to prepare filter layer A; mesoporous γ-alumina is used to further perform the first step of adsorption filtration on SO2 and NO in flue gas, thereby improving the overall adsorption performance of the filter material. Since mesoporous ρ-alumina is used as a binder, its dehydration rate in the water splash process is too fast during the hydration process, and its strong bonding performance makes it easy to agglomerate during the mixing process of the mixed slurry to form tiny particles, resulting in uneven dispersion of composite MOF and mesoporous γ-alumina. Adding citric acid can reduce the hydration inhibition of mesoporous ρ-alumina, which helps to delay the hydration of HA, achieve a better balance between bonding performance and hydration rate, greatly improve the dispersion performance and processing performance of each component of filter layer A, facilitate the production of filter layer A, and improve production efficiency.
[0029] In order to enhance the bonding performance and high temperature resistance between the filter layer A and the filter layer B, the present invention is composed of polyimide and polytetrafluoroethylene as the main components, and the main chain thereof contains an imide group, resulting in a higher thermal decomposition temperature. The addition of polytetrafluoroethylene greatly improves the compatibility of the adhesive in the filter layer B. During the hot pressing curing process, the entire bonding surface and the filter layer B become a whole, and the traditional sandwich structure is changed into a "mortise and tenon structure" combined with the filter layer A, which greatly improves the high temperature resistance and bonding performance of the filter material. The present invention uses a venturi tube and compressed air to spray on the surface and inside of the filter layer B, in order to use tourmaline particles to promote the fiber refinement of the polytetrafluoroethylene in the filter layer B, thereby avoiding the occurrence of the problem of filter material clogging caused by the polytetrafluoroethylene emulsion adhesive in the filter layer B. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the following examples, polyvinyl pyrrolidone was purchased from Sinopharm Chemical Reagent Co., Ltd.; triblock copolymer model P123 was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; polytetrafluoroethylene filter material was purchased from Huzhou Senno Fluoride Material Technology Co., Ltd., China; polytetrafluoroethylene dispersion solution 60wt% was purchased from Aladdin Industrial Co., Ltd., China. Polyimide was purchased from Suzhou Pinyu Optoelectronics Technology Co., Ltd., China; tourmaline particles were purchased from Guilin Tourmaline New Materials Co., Ltd.; and the remaining raw materials were commercially available.
[0032] The preparation method of mesoporous ρ-alumina comprises the following steps: dropping aluminum hydroxide particles with a particle size of 7 mm into a tubular furnace that has been preheated to a temperature of 1000K under ultrasonic vibration conditions, pyrolyzing for 5 seconds, collecting powder at the bottom of the furnace, and measuring the powder packing density to obtain mesoporous ρ-alumina; the mesoporous ρ-alumina is sealed in a polypropylene bottle and stored for future use.
[0033] Example 1: A method for preparing a flue gas filter material for a coal-fired power plant: S1: 1 g of copper sulfate trihydrate, 0.25 g of 5-aminoisophthalic acid and 0.75 g of tris-benzoic acid were added to 20 mL of a mixed solvent, ultrasonically dispersed, heated to 85°C for reaction for 20 h, filtered, washed alternately with N,N-dimethylformamide and ethanol, and vacuum dried at 80°C to obtain an amino copper-based MOF;
[0034] S2: Add 1g of polyvinyl pyrrolidone to 20mL of methanol and stir evenly, add 0.4g of amino copper-based MOF and 1.24g of zinc nitrate hexahydrate and stir evenly to obtain solution A; add 0.546g of 2-methylimidazole and 0.902g of 2-aminobenzimidazole to 20mL of methanol and stir evenly to obtain solution B; add solution B to solution A, stir and react for 1.5h, filter, wash with methanol, and vacuum dry at 80°C to obtain a composite MOF;
[0035] S3: 1 g of the triblock copolymer was added to anhydrous ethanol, stirred for 6 h, 1.41 g of 65-68 wt % nitric acid and 2 g of aluminum isopropoxide were added, the reaction vessel was completely covered with a polyvinyl alcohol film, stirred at room temperature for 24 h, the film was removed and the solvent was evaporated at 60 °C, aged for 3 d, the aged product was heated to 700 °C and calcined for 4 h, crushed, and sieved to obtain mesoporous γ-alumina;
[0036] S4: 100 g of composite MOF, 20 g of mesoporous γ-alumina, 5 g of mesoporous ρ-alumina, 0.012 g of citric acid, and 5 g of deionized water were added into a container and mixed evenly, and the mixed slurry was added into a mold, and vacuum dried at 110° C. for 12 h to obtain a filter layer A;
[0037] S5: immerse the polytetrafluoroethylene filter material in a 0.8wt% sodium alginate solution, vacuum filter, take it out, squeeze the filter material with a metal roller to remove excess sodium alginate solution, and vacuum dry it at 60°C for 24h to obtain a modified polytetrafluoroethylene filter material; immerse the modified polytetrafluoroethylene filter material in a 0.07mol / L mixed solution of manganese nitrate and cerium nitrate, vacuum filter, remove it, and vacuum dry it at 200°C for 60min to obtain filter layer B;
[0038] S6: Spray the tourmaline particles onto the surface of filter layer B through a venturi tube and compressed air, with a spraying amount of 12.5 g / cm 2 The sprayed filter layer B was immersed in 10wt% polytetrafluoroethylene emulsion, taken out, and the excess polytetrafluoroethylene emulsion was removed by squeezing the filter material with a metal roller, and it was hot-pressed and compounded with the 8μm filter layer A coated with 70wt% polyimide and 30wt% polytetrafluoroethylene emulsion to obtain a flue gas filter material.
[0039] Example 2: A method for preparing a flue gas filter material for a coal-fired power plant: S4: 110 g of composite MOF, 35 g of mesoporous γ-alumina, 18 g of mesoporous ρ-alumina, 0.048 g of citric acid, and 15 g of deionized water are added to a container and mixed evenly, the mixed slurry is added to a mold, and vacuum dried at 110° C. for 12 h to obtain a filter layer A;
[0040] The remaining steps are the same as those in Example 1.
[0041] Example 3: A method for preparing a flue gas filter material for a coal-fired power plant: S4: 120 g of composite MOF, 50 g of mesoporous γ-alumina, 24 g of mesoporous ρ-alumina, 0.062 g of citric acid, and 20 g of deionized water are added to a container and mixed evenly, the mixed slurry is added to a mold, and vacuum dried at 110° C. for 12 h to obtain a filter layer A;
[0042] The remaining steps are the same as those in Example 1.
[0043] Comparative Example 1: A method for preparing a flue gas filter material for a coal-fired power plant: S1: 1 g of copper sulfate trihydrate, 0.25 g of 5-aminoisophthalic acid and 0.75 g of tris-benzoic acid were added to 20 mL of a mixed solvent, ultrasonically dispersed, heated to 85°C for reaction for 20 h, filtered, washed alternately with N,N-dimethylformamide and ethanol, and vacuum dried at 80°C to obtain an amino copper-based MOF;
[0044] S2: Add 1g of polyvinyl pyrrolidone to 20mL of methanol and stir evenly, add 0.4g of amino copper-based MOF and 1.24g of zinc nitrate hexahydrate and stir evenly to obtain solution A; add 0.546g of 2-methylimidazole and 0.902g of 2-aminobenzimidazole to 20mL of methanol and stir evenly to obtain solution B; add solution B to solution A, stir and react for 1.5h, filter, wash with methanol, and vacuum dry at 80°C to obtain a composite MOF;
[0045] S3: 1 g of the triblock copolymer was added to anhydrous ethanol, stirred for 6 h, 1.41 g of 65-68 wt % nitric acid and 2 g of aluminum isopropoxide were added, the reaction vessel was completely covered with a polyvinyl alcohol film, stirred at room temperature for 24 h, the film was removed and the solvent was evaporated at 60 °C, aged for 3 d, the aged product was heated to 700 °C and calcined for 4 h, crushed, and sieved to obtain mesoporous γ-alumina;
[0046] S4: 100 g of composite MOF, 20 g of mesoporous γ-alumina, 5 g of mesoporous ρ-alumina, 0.012 g of citric acid, and 5 g of deionized water were added into a container and mixed evenly, and the mixed slurry was added into a mold, and vacuum dried at 110° C. for 12 h to obtain a filter layer A;
[0047] S5: immersing the polytetrafluoroethylene filter material in a 0.07 mol / L mixed solution of manganese nitrate and cerium nitrate, vacuum filtering, removing, and vacuum drying at 200° C. for 60 min to obtain filter layer B;
[0048] S6: Spray the tourmaline particles onto the surface of filter layer B through a venturi tube and compressed air, with a spraying amount of 12.5 g / cm 2The sprayed filter layer B was immersed in 10wt% polytetrafluoroethylene emulsion, taken out, and the excess polytetrafluoroethylene emulsion was removed by squeezing the filter material with a metal roller, and it was hot-pressed and compounded with the 8μm filter layer A coated with 70wt% polyimide and 30wt% polytetrafluoroethylene emulsion to obtain a flue gas filter material.
[0049] Comparative Example 2: A method for preparing a flue gas filter material for a coal-fired power plant: S1: 1 g of copper sulfate trihydrate, 0.25 g of 5-aminoisophthalic acid and 0.75 g of tris-benzoic acid were added to 20 mL of a mixed solvent, ultrasonically dispersed, heated to 85°C for reaction for 20 h, filtered, washed alternately with N,N-dimethylformamide and ethanol, and vacuum dried at 80°C to obtain an amino copper-based MOF;
[0050] S2: 1 g of the triblock copolymer was added to anhydrous ethanol, stirred for 6 h, 1.41 g of 65-68 wt % nitric acid and 2 g of aluminum isopropoxide were added, the reaction vessel was completely covered with a polyvinyl alcohol film, stirred at room temperature for 24 h, the film was removed and the solvent was evaporated at 60 °C, aged for 3 d, the aged product was heated to 700 °C and calcined for 4 h, crushed, and sieved to obtain mesoporous γ-alumina;
[0051] S3: 100 g amino copper-based MOF, 20 g mesoporous γ-alumina, 5 g mesoporous ρ-alumina, 0.012 g citric acid, and 5 g deionized water were added to a container and mixed evenly, the mixed slurry was added to a mold, and vacuum dried at 110° C. for 12 h to obtain a filter layer A;
[0052] S4: immerse the polytetrafluoroethylene filter material in a 0.8wt% sodium alginate solution, vacuum filter, take it out, squeeze the filter material with a metal roller to remove excess sodium alginate solution, and vacuum dry it at 60°C for 24h to obtain a modified polytetrafluoroethylene filter material; immerse the modified polytetrafluoroethylene filter material in a 0.07mol / L mixed solution of manganese nitrate and cerium nitrate, vacuum filter, remove it, and vacuum dry it at 200°C for 60min to obtain filter layer B;
[0053] S5: Spray the tourmaline particles onto the surface of filter layer B through a venturi tube and compressed air, with a spraying amount of 12.5 g / cm 2 The sprayed filter layer B was immersed in 10wt% polytetrafluoroethylene emulsion, taken out, and the excess polytetrafluoroethylene emulsion was removed by squeezing the filter material with a metal roller, and it was hot-pressed and compounded with the 8μm filter layer A coated with 70wt% polyimide and 30wt% polytetrafluoroethylene emulsion to obtain a flue gas filter material.
[0054] Comparative Example 3: A method for preparing a flue gas filter material for a coal-fired power plant: S1: 1 g of copper sulfate trihydrate, 0.25 g of 5-aminoisophthalic acid and 0.75 g of tris-benzoic acid were added to 20 mL of a mixed solvent, ultrasonically dispersed, heated to 85°C for reaction for 20 h, filtered, washed alternately with N,N-dimethylformamide and ethanol, and vacuum dried at 80°C to obtain an amino copper-based MOF;
[0055] S2: Add 1g of polyvinyl pyrrolidone to 20mL of methanol and stir evenly, add 0.4g of amino copper-based MOF and 1.24g of zinc nitrate hexahydrate and stir evenly to obtain solution A; add 0.546g of 2-methylimidazole and 0.902g of 2-aminobenzimidazole to 20mL of methanol and stir evenly to obtain solution B; add solution B to solution A, stir and react for 1.5h, filter, wash with methanol, and vacuum dry at 80°C to obtain a composite MOF;
[0056] S3: 1 g of the triblock copolymer was added to anhydrous ethanol, stirred for 6 h, 1.41 g of 65-68 wt % nitric acid and 2 g of aluminum isopropoxide were added, the reaction vessel was completely covered with a polyvinyl alcohol film, stirred at room temperature for 24 h, the film was removed and the solvent was evaporated at 60 °C, aged for 3 d, the aged product was heated to 700 °C and calcined for 4 h, crushed, and sieved to obtain mesoporous γ-alumina;
[0057] S4: 100 g of composite MOF, 20 g of mesoporous γ-alumina, 5 g of mesoporous ρ-alumina, and 5 g of deionized water were added into a container and mixed evenly, the mixed slurry was added into a mold, and vacuum dried at 110° C. for 12 h to obtain a filter layer A;
[0058] S5: immerse the polytetrafluoroethylene filter material in a 0.8wt% sodium alginate solution, vacuum filter, take it out, squeeze the filter material with a metal roller to remove excess sodium alginate solution, and vacuum dry it at 60°C for 24h to obtain a modified polytetrafluoroethylene filter material; immerse the modified polytetrafluoroethylene filter material in a 0.07mol / L mixed solution of manganese nitrate and cerium nitrate, vacuum filter, remove it, and vacuum dry it at 200°C for 60min to obtain filter layer B;
[0059] S6: Spray the tourmaline particles onto the surface of filter layer B through a venturi tube and compressed air, with a spraying amount of 12.5 g / cm 2 The sprayed filter layer B was immersed in 10wt% polytetrafluoroethylene emulsion, taken out, and the excess polytetrafluoroethylene emulsion was removed by squeezing the filter material with a metal roller, and it was hot-pressed and compounded with the 8μm filter layer A coated with 70wt% polyimide and 30wt% polytetrafluoroethylene emulsion to obtain a flue gas filter material.
[0060] Comparative Example 4: A method for preparing a flue gas filter material for a coal-fired power plant: S1: 1 g of copper sulfate trihydrate, 0.25 g of 5-aminoisophthalic acid and 0.75 g of tris-benzoic acid were added to 20 mL of a mixed solvent, ultrasonically dispersed, heated to 85°C for reaction for 20 h, filtered, washed alternately with N,N-dimethylformamide and ethanol, and vacuum dried at 80°C to obtain an amino copper-based MOF;
[0061] S2: Add 1g of polyvinyl pyrrolidone to 20mL of methanol and stir evenly, add 0.4g of amino copper-based MOF and 1.24g of zinc nitrate hexahydrate and stir evenly to obtain solution A; add 0.546g of 2-methylimidazole and 0.902g of 2-aminobenzimidazole to 20mL of methanol and stir evenly to obtain solution B; add solution B to solution A, stir and react for 1.5h, filter, wash with methanol, and vacuum dry at 80°C to obtain a composite MOF;
[0062] S3: 1 g of the triblock copolymer was added to anhydrous ethanol, stirred for 6 h, 1.41 g of 65-68 wt % nitric acid and 2 g of aluminum isopropoxide were added, the reaction vessel was completely covered with a polyvinyl alcohol film, stirred at room temperature for 24 h, the film was removed and the solvent was evaporated at 60 °C, aged for 3 d, the aged product was heated to 700 °C and calcined for 4 h, crushed, and sieved to obtain mesoporous γ-alumina;
[0063] S4: 100 g of composite MOF, 20 g of mesoporous γ-alumina, 5 g of mesoporous ρ-alumina, 0.012 g of citric acid, and 5 g of deionized water were added into a container and mixed evenly, and the mixed slurry was added into a mold, and vacuum dried at 110° C. for 12 h to obtain a filter layer A;
[0064] S5: immerse the polytetrafluoroethylene filter material in a 0.8wt% sodium alginate solution, vacuum filter, take it out, squeeze the filter material with a metal roller to remove excess sodium alginate solution, and vacuum dry it at 60°C for 24h to obtain a modified polytetrafluoroethylene filter material; immerse the modified polytetrafluoroethylene filter material in a 0.07mol / L mixed solution of manganese nitrate and cerium nitrate, vacuum filter, remove it, and vacuum dry it at 200°C for 60min to obtain filter layer B;
[0065] S6: Immerse the filter layer B in 10wt% polytetrafluoroethylene emulsion, take it out, squeeze the filter material with a metal roller to remove excess polytetrafluoroethylene emulsion, and hot-press it with the 8μm filter layer A coated with 70wt% polyimide and 30wt% polytetrafluoroethylene emulsion to obtain a flue gas filter material.
[0066] Experiment: A flue gas purification module with a sandwich structure is made by using flue gas filter material as the inner lining and polytetrafluoroethylene filter material as the outer protective net. The module size is Φ180×H3000mm. The flue gas purification module is connected to the flue gas temporary storage device. The prepared SO2 concentration is 5000mg / m3 , NO concentration is 1000mg / m 3 , mixed with air moisture, the experimental flue gas with a temperature of 200°C is injected into the flue gas generating device and the SO2 concentration and NO concentration are detected; the experimental flue gas is passed into the flue gas purification module, the exhaust flue gas is mixed with air and then passes through the pipeline of the detection sensor to detect the SO2 and NO in the exhaust gas x Concentration. Calculate the adsorption removal rate, removal rate = 1-(concentration after adsorption / concentration before adsorption) × 100%; the experimental data are shown in Table 1 below;
[0067] Table 1 Flue gas filtration experimental data table
[0068]
[0069] Conclusion: The flue gas filter material prepared by the present invention has excellent high temperature resistant desulfurization and denitrification filtration performance.
[0070] In Comparative Example 1, sodium alginate and vacuum filtration were not used to jointly treat the polytetrafluoroethylene filter material, resulting in a decrease in the loading amount of the Mn and Ce-based metal catalysts, resulting in a decrease in the removal and adsorption performance.
[0071] Comparative Example 2: The amino copper-based MOF lacks the outer shell ZIF-8 structure, and the single MOF structure is easily disintegrated by water impact, resulting in reduced removal and adsorption performance;
[0072] Comparative Example 3: The component in the filter layer A lacks citric acid, resulting in the formation of fine spherical particles inside the mixed slurry, which are unevenly dispersed and result in reduced removal and adsorption performance;
[0073] In Comparative Example 4, tourmaline particles were not sprayed on the surface of the filter layer B through the venturi tube and compressed air. The polytetrafluoroethylene emulsion in the adhesive easily blocked the pores of the filter material, resulting in reduced removal and adsorption performance.
[0074] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a flue gas filter material for a coal-fired power plant, characterized in that: The following steps are involved: S1: adding composite MOF, mesoporous γ-alumina, mesoporous ρ-alumina, citric acid and deionized water into a container and mixing them evenly, adding the mixed slurry into a mold, and vacuum drying to obtain a filter layer A; S2: immersing the polytetrafluoroethylene filter material in the sodium alginate solution, vacuum filtering, taking out, and vacuum drying to obtain a modified polytetrafluoroethylene filter material; The modified polytetrafluoroethylene filter material is immersed in a mixed solution of manganese nitrate and cerium nitrate, vacuum filtered, removed, and vacuum dried to obtain a filter layer B; S3: spraying tourmaline particles on the surface of the filter layer B, immersing the sprayed filter layer B in a polytetrafluoroethylene emulsion, taking it out, hot-pressing and compounding it with the filter layer A coated with a polyimide emulsion, and drying it at 150-230° C. for 30-60 min to obtain a flue gas filter material; The preparation method of the composite MOF comprises the following steps: Add polyvinyl pyrrolidone to methanol and stir evenly, add amino copper-based MOF and zinc nitrate hexahydrate and stir evenly to obtain solution A; add 2-methylimidazole and 2-aminobenzimidazole to methanol and stir evenly to obtain solution B; add solution B to solution A, stir and react for 1.5-2h, filter, wash with methanol, and vacuum dry to obtain a composite MOF; The preparation method of the amino copper-based MOF comprises the following steps: adding copper sulfate trihydrate, 5-aminoisophthalic acid and trimesic acid into a mixed solvent, ultrasonically dispersing, heating to 85-90° C. for reaction for 20-22 hours, filtering, washing alternately with N,N-dimethylformamide and ethanol, and vacuum drying to obtain the amino copper-based MOF.
2. The method for preparing a flue gas filter material for a coal-fired power plant according to claim 1, characterized in that: In the solution A, the mass ratio of amino copper-based MOF: polyvinyl pyrrolidone: zinc nitrate hexahydrate is 1: (0.2-0.4): (0.31-1.24); in the solution B, the mass ratio of 2-methylimidazole: 2-aminobenzimidazole is (0.546-2.18): (0.225-0.902).
3. The method for preparing a flue gas filter material for a coal-fired power plant according to claim 1, characterized in that: In the amino copper-based MOF, the mass ratio of copper sulfate trihydrate: 5-aminoisophthalic acid: trimesic acid is 1: (0.25-0.5): (0.75-1).
4. The method for preparing a flue gas filter material for a coal-fired power plant according to claim 1, characterized in that: The preparation method of the mesoporous γ-alumina comprises the following steps: The triblock copolymer is added to anhydrous ethanol, stirred for 6-8 hours, 65-68wt% nitric acid and aluminum isopropoxide are added, the reaction container is completely covered with a polyvinyl alcohol film, stirred at room temperature for 24 hours, the film is removed to evaporate the solvent, aged for 3 days, the aged product is heated to 700-705°C and calcined for 4-4.5 hours, crushed, and sieved to obtain mesoporous γ-alumina; In the mesoporous γ-alumina, the mass ratio of triblock copolymer to aluminum isopropoxide is (1-2):(2-4).
5. The method for preparing a flue gas filter material for a coal-fired power plant according to claim 1, characterized in that: In step S2, the concentration of the sodium alginate solution is 0.8-1.0wt%, and the immersion time is 60-65min; the concentration of cerium in the mixed solution is 0.07-0.08mol / L, the molar ratio of manganese to cerium is 6:1, and the immersion time is 60-65min.
6. The method for preparing a flue gas filter material for a coal-fired power plant according to claim 1, characterized in that: The spraying method includes spraying tourmaline particles on the surface of the filter layer B through a venturi tube and compressed air; the spraying content of the tourmaline particles is 12.5-15g / cm 2 The concentration of the polytetrafluoroethylene emulsion is 10-12wt%; the polyimide emulsion composition includes 70-85wt% polyimide and 15-30wt% polytetrafluoroethylene; the hot pressing composite temperature is 200-210°C, the hot pressing pressure is 1.5-1.6MPa, and the hot pressing time is 30-45s.
7. A flue gas filter material prepared according to the method for preparing a flue gas filter material for a coal-fired power plant according to any one of claims 1 to 6.
Citation Information
Patent Citations
Method for separating acid gases using metal-organic frameworks impregnated with amines
CN102361678A
Ultrafast high space-time-yield synthesis of metal-organic frameworks
CN108290134A